Ownership structure and corporate strategy: one question viewed from two different worlds - Lane, Peter J.; Cannella, Albert A.; Lubatkin, Michael (Strategic Management Journal, 1999)
In their response to our paper, Amihud and Lev (1999) and Denis, Denis, and Sarin (1999) claim that disciplinary differences don’t matter and that methods and evidence should speak for themselves. In contrast, we argue that important differences exist between financial economics and strategic management, leading to differing beliefs, norms, methods, and interpretations of empirical results. Using a strategic management perspective to review the evidence presented by Amihud and Lev in their earlier study (1981) and in their and Denis et al.’s critiques of our work (1999), we find no reason to revise our original conclusion: there is little theoretical or empirical basis for believing that monitoring by a firm’s principals influences its diversification strategy and acquisition decisions. Copyright © 1999 John Wiley & Sons, Ltd.